PENGEMBANGAN ALAT PERAGA PAPAN KARTU AIKA ̅ PADA KONTEN NUMERASI KERAJAAN MARTAPURA UNTUK SISWA SMP - Puspitasari, Emelia; Kurniawan, Kurniawan (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2024)
Class VII students at SMP Negeri 31 Samarinda like learning mathematics which is linked to local culture. However, they do not yet know the numbers from their own area. The introduction to ancient numbers is presented in an interesting way using visual aids. This research aims to determine the development process, level of validity, and level of practicality of the resulting product, namely the Card Board. This Research and Development (R&D) research uses the ADDIE model, namely analysis, design, development, implementation, evaluation. Data collection techniques include needs analysis questionnaires, interviews, validation instruments and practicality instruments. The data analysis techniques used are qualitative descriptive and quantitative descriptive. This research has two subjects, namely the validation subject consisting of experts and the practical subject consisting of 10 class VII students at SMPN 31 Samarinda. Based on the research results, it was concluded that the product development process went through the stages of analysis, design and development, the product met the very valid criteria based on the assessment of Mathematics material experts, History material experts and media experts with average percentages respectively of 87.3%, 98, 98. 3%, and 92%, and was declared very practical based on student responses with an average percentage of 90.04%.